Role of gradient echo sequence in delineation of Thenar muscles anatomy - Sidek, Sabrilhakim; Roslan, Muhammad Rozaidi; Sidek, Shahrul Na'im (2017)
Magnetic Resonance Imaging (MRI) is known to be the imaging modality of choice to assess human muscles anatomy superior to other modalities (eg: ultrasound and CT scan) due to its excellent ability to differentiate soft tissue contrast, good spatial resolution and wider field of view with no radiation effect. To date, proton Density (PD), T1W and T2W sequences are been utilised to assess muscular structures. However, delineation of each thenar muscle which are small in size can be difficult using these sequences.